The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.21859/mci-01043
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor Effects of Essential Oils of Red Clover and Ragweed on MCF-7 Breast Cancer Cell Line

Abstract: Introduction: Breast cancer is one of the most common malignancies among Iranian women. Nowadays, the use of traditional medicinal plants has emerged as a tempting complementary to the treatment of breast cancer due to minimal side effects and less documented drug resistance. The aim of this study was to examine the anticancer effects of the essential oils of red clover and mature fruit of Bassia scoparia on MCF-7 cells. Methods: Essential oils were extracted from Bassia scoparia and red clover plants, by a Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The main compounds were α-thujaplicin (22.91%), phytone (8.66%), dictamnol (7.98%), butylated hydroxytoluene (7.49%), phytol (6.57%) and camphenolone (3.84%) (El-Shamy et al 2012). Kianinodeh et al (2017) observed a similar qualitative composition of the essential oil of B. scoparia. However, the essential oil obtained from the fruits of the plant that grows in Iran differed in its quantitative composition because it contained alkanes (n- 2000).…”
Section: Other Compoundsmentioning
confidence: 63%
See 4 more Smart Citations
“…The main compounds were α-thujaplicin (22.91%), phytone (8.66%), dictamnol (7.98%), butylated hydroxytoluene (7.49%), phytol (6.57%) and camphenolone (3.84%) (El-Shamy et al 2012). Kianinodeh et al (2017) observed a similar qualitative composition of the essential oil of B. scoparia. However, the essential oil obtained from the fruits of the plant that grows in Iran differed in its quantitative composition because it contained alkanes (n- 2000).…”
Section: Other Compoundsmentioning
confidence: 63%
“…Furthermore, incubation of MCF-7 cells with essential oil resulted in changes in cellular morphology, manifested as star-shaped cells, vacuolation, cytoplasmic and cellular shrinkage. Pyknotic nuclei were also observed, suggesting stimulation of apoptosis in cells (Kianinodeh et al 2017).…”
Section: Cytotoxic Activitymentioning
confidence: 97%
See 3 more Smart Citations